2022
DOI: 10.1371/journal.pone.0272292
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors of participation and success rates in research funding competitions: Case study

Abstract: Research and innovation play a key role in generating smart and sustainable economic growth. By producing new knowledge, the research contributes to the development of new and innovative products, processes, and services, which in turn lead to increased productivity, industrial competitiveness, and, ultimately, the prosperity of the community as a whole. However, all research, development and innovation activities depend on the financial resources made available, as specific financing accelerates the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The findings and themes discussed above align with several literature sources. These go in line with Rusu et al (2022) along with Wiebe and Maticka-Tyndale (2017) who identified the determining factors for the researcher's participation and success rates in research funding competitions and discussed various strategies and best practices for improving grant-writing skills, fostering collaboration, and providing institutional support. This study findings are consistent with Shamsi and Osam (2022) who focus on the importance of language support for non-native English-speaking researchers.…”
Section: Comparing Survey Findings With Interview Themesmentioning
confidence: 68%
“…The findings and themes discussed above align with several literature sources. These go in line with Rusu et al (2022) along with Wiebe and Maticka-Tyndale (2017) who identified the determining factors for the researcher's participation and success rates in research funding competitions and discussed various strategies and best practices for improving grant-writing skills, fostering collaboration, and providing institutional support. This study findings are consistent with Shamsi and Osam (2022) who focus on the importance of language support for non-native English-speaking researchers.…”
Section: Comparing Survey Findings With Interview Themesmentioning
confidence: 68%
“…In addition, working in a well-recognized research institution seems to be a positive characteristic for increasing the odds of getting a research proposal funded ( 26 ). Researchers in the beginning of their career may improve their chances of getting funded by collaborating with accomplished investigators ( 23 , 30 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, working in a well-recognized research institution seems to be a positive characteristic for increasing the odds of getting a research proposal funded (26). Researchers in the beginning of their career may improve their chances of getting funded by collaborating with accomplished investigators (23,30,32) 8. Patient and public involvement: Research that involves the public or patients in its design and execution can provide real-world context and relevance.…”
Section: Strong Research Teammentioning
confidence: 99%
“…Research funding has been viewed as a key determinant of scientific activity (Rusu et al, 2022), and can have a long-Funding affords researchers essential resources and opportunities to establish themselves in their fields and pursue their research goals (Jacob & Lefgren, 2011). Moreover, the research funding success has been shown to be consistent with the Matthew effect and the Halo effect (Liao, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research funding has been viewed as a key determinant of scientific activity (Rusu et al, 2022), and can have a long‐term and vital impact on the trajectory of researchers’ careers. Funding affords researchers essential resources and opportunities to establish themselves in their fields and pursue their research goals (Jacob & Lefgren, 2011).…”
Section: Introductionmentioning
confidence: 99%